Karakteristik kimia dan fungsional minuman instan kecambah kedelai terfortifikasi kalsium - Siti Aminah; Hersanti Sulistyaningrum; Rohadi Rohadi (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
The bioactive components of soybean sprouts have been known to provide health benefits. The functional product that can be developed is instant soybean sprout milk through an encapsulation process using a spray dryer. This product can have its functional and nutritional value increased through fortification. Calcium is a fortifier that can be used to increase the calcium of soybean sprout milk. This research aims to determine the chemical and functional composition (vitamins C and E) as well as the antioxidant activity of instant soybean sprout milk fortified with calcium. Three types of calcium used are: calcium: lactate, carbonate and chloride, each with 4 concentration levels (0.3%; 0.6 %; 0.9% and 1.2%). The results showed that calcium fortification had an effect on chemical composition, vitamin C, vitamin E and antioxidant activity. Fortification with calcium lactate provides the highest results in chemical composition including levels of: ash, fat, protein, crude fiber, vitamins C and E and antioxidant activity.